2021
DOI: 10.3390/foods10020231
|View full text |Cite
|
Sign up to set email alerts
|

Emotions Evoked by Colors and Health Functionality Information of Colored Rice: A Cross-Cultural Study

Abstract: This study aimed to examine the emotional responses evoked by cooked colored rice and its health functionality information in both consumers who eat rice as a staple food and consumers who do not eat rice as a staple food. Specifically, Korean and American consumers were exposed to colored rice and its health functionality information and an emotion lexicon was generated and measured based on focus group interviews (FGI) and two online consumer surveys. In test 1, the emotions evoked by presentation of stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…For Korean participants, to minimize a potential gap between original (English) and translated versions of the emotion terms, both Korean and English versions of the 12 pairs of emotion terms were presented. The 12 pairs of emotion terms, with the assistance of bilingual individuals proficient in both English and Korean, were translated into Korean based on previous studies that utilized Korean versions of self-reported emotion questionnaires, including the EsSense Profile ® [55] and the Coffee Drinking Experience questionnaire [56]. Prior to the main test, clarity of the translated terms was also checked with Korean individuals.…”
Section: Methodsmentioning
confidence: 99%
“…For Korean participants, to minimize a potential gap between original (English) and translated versions of the emotion terms, both Korean and English versions of the 12 pairs of emotion terms were presented. The 12 pairs of emotion terms, with the assistance of bilingual individuals proficient in both English and Korean, were translated into Korean based on previous studies that utilized Korean versions of self-reported emotion questionnaires, including the EsSense Profile ® [55] and the Coffee Drinking Experience questionnaire [56]. Prior to the main test, clarity of the translated terms was also checked with Korean individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Although the EsSense profile ® and the WellSense Profile TM methods have been widely used, the application of these methods in in countries with different cultures and languages should be appropriately performed. For this reason, cross-cultural studies of emotion elicited by food have gained attention [12][13][14]. However, research investigating the impact of questionnaire design and measurement scales on emotion and wellness profiles is scarce.…”
Section: Introductionmentioning
confidence: 99%